2002
DOI: 10.1002/gcc.10136
|View full text |Cite
|
Sign up to set email alerts
|

A novel chromosomal inversion at 11q23 in infant acute myeloid leukemia fuses MLL to CALM, a gene that encodes a clathrin assembly protein

Abstract: Rearrangements involving the MLL gene at chromosome band 11q23 are common in infant acute myeloid leukemias (AMLs). We recently encountered an infant patient with rapidly progressive AML whose leukemic cells harbored a previously undescribed MLL rearrangement involving an inversion of 11q [inv(11)(q14q23)]. We used panhandle PCR to determine that this rearrangement juxtaposed the MLL (Mixed-Lineage Leukemia) gene to the CALM (Clathrin Assembly Lymphoid Myeloid leukemia) gene at 11q14-q21. The CALM protein part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 46 publications
(56 reference statements)
0
30
0
Order By: Relevance
“…24 A single case report described an MLL-CALM fusion in a 12-week-old Caucasian female who presented with rapidly progressive acute myeloid leukemia (AML). 25 In this study, the authors used panhandle PCR to determine that MLL was fused to CALM at 11q14-q21. By assaying RNA from the patient's leukemic cells, fusion transcripts were identified.…”
Section: Introductionmentioning
confidence: 99%
“…24 A single case report described an MLL-CALM fusion in a 12-week-old Caucasian female who presented with rapidly progressive acute myeloid leukemia (AML). 25 In this study, the authors used panhandle PCR to determine that MLL was fused to CALM at 11q14-q21. By assaying RNA from the patient's leukemic cells, fusion transcripts were identified.…”
Section: Introductionmentioning
confidence: 99%
“…CALM has also been shown to be fused to MLL, in a unique case of t(10;11)(p13;q23) observed in an infant AML. 6 AF10 was first identified as a fusion partner of MLL in AMLs. 7,8 AF10 is expressed ubiquitously and codes for a protein of 1027 aa.…”
Section: Introductionmentioning
confidence: 99%
“…A definite role of CALM in endocytic vesicle formation has been demonstrated by the ability of over-expressed CALM to interfere with endocytosis of receptors for both transferrin and epidermal growth factor [15]. Wechsler et al reported MLL-CALM fusion transcript involving an inversion 11q [inv (11)(q14q23)] associated with infant AML leukemogenesis [16]. Chromosomal abnormality of 11, del (11)(11q14q23), was continuously detected every time we examined the patient.…”
Section: Discussionmentioning
confidence: 98%